UAV-borne SAR motion compensation by GPS+IMU - Heng, Choon Kian (2016)
The Synthetic Aperture Radar (SAR) is delegated as one of the high determination imaging system in microwave remote detecting. The operational components of SAR, which is different to optical detecting, comprise of an expansive number of frequency-modulated received echoes. It must be acquired in real time. As of late, airborne unmanned aerial vehicle (UAV) was usually showed up in SAR applications for information procurement purposes. Supposition was made on the ostensible direction of the airborne UAV to be straight line way. In reality, be that as it may, such suspicion will not hold because of air turbulence and UAV's movement mistake, which brings about extreme debasement in yield pictures quality. In this project, a global positioning satellite (GPS) was utilized to detect and repay the movement blunders of the airborne UAVSAR. By using GPS+IMU, motion is compensated for SAR.